Duplications in the G3 domain or switch II region in HRAS identified in patients with Costello syndrome. Issue 1 (11th October 2021) - Nagai, Koki; Niihori, Tetsuya; Okamoto, Nobuhiko; Kondo, Akane; Suga, Kenichi; Ohhira, Tomoko; Hayabuchi, Yasunobu; Homma, Yukako; Nakagawa, Ryuji; Ifuku, Toshinobu; Abe, Taiki; Mizuguchi, Takeshi; et al.
Abstract: Costello syndrome (CS) is an autosomal‐dominant disorder characterized by distinctive facial features, hypertrophic cardiomyopathy, skeletal abnormalities, intellectual disability, and predisposition to cancers. Germline variants in HRAS have been identified in patients with CS. Intragenic HRAS duplications have been reported in three patients with a milder phenotype of CS. In this study, we identified two known HRAS variants, p.(Glu63_Asp69dup), p.(Glu62_Arg68dup), and one novel HRAS variant, p.(Ile55_Asp57dup), in patients with CS, including a patient with craniosynostosis. These intragenic duplications are located in the G3 domain and the switch II region. Cells expressing cDNA with these three intragenic duplications showed an increase in ELK‐1 transactivation. Injection of wild‐type or mutant HRAS mRNAs with intragenic duplications in zebrafish embryos showed significant elongation of the yolk at 11 h postfertilization, which was improved by MEK inhibitor treatment, and a variety of developmental abnormalities at 3 days post fertilization was observed. These results indicate that small in‐frame duplications affecting the G3 domain and switch II region of HRAS increase the activation of the ERK pathway, resulting in developmental abnormalities in zebrafish or patients with CS. Abstract : In this study, we identified three intragenic HRAS duplications, including a novel p.(Ile55_Asp57dup) duplication, in three patients with a phenotype related to Costello syndrome. Zebrafish experiments showed that these intragenic duplications affect developmental processes. MEK inhibitor was able to revert the abnormality. Our data indicate that these intragenic HRAS duplications could increase the activation of the ERK pathway.